Six employment relationship practices for sustaining organizational performance - Noor Syakirah Zakaria; Mohd Khairuddin Hashim (Penerbit UMS, 2017)
Organizations need to develop as well as strengthen their employment relations in order to improve not only their performance, but also their competitiveness. Despite the importance of employment relations to organizations, the literature reveals there is not much information on how companies practice employment relations. The limited information has resulted from lack of emphasis on the important role of employment relations in organizations. This paper specifically attempts to address this issue by providing insights into six important employment relations practices that can help sustain the performance of organizations. The six practices were identified based on the review of the literature and findings of previous studies.